Systematic Literature Review on Factors Causing Secondary Students` Absenteeism - Muhammad Najib Husman @ Othman; Ahmad Jazimin Jusoh; Mohamad Aziz Shah Mohamed Arip (Peneliti.net, 2023)
The literature reviews to identify the factors causing secondary student absenteeism which is still scarce and insufficient. The objective of study was to investigate the factors causing absenteeism of secondary school students. The methodology used in this study was systematic literature review. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) were implemented for selection, screening, and reporting. This study reviewed quantitative research released between 2018 and 2022. The databases were used such as Web of Science (WOS), SCOPUS, ERIC and Google Scholar. The most keywords were used secondary students, absenteeism, were the most used keywords. Results of study showed that there were eleven factors of causing secondary students` absenteeism, including mental health, bullying, teacher, school, friends, parents, substance use, physical fight, school climate, technology academic challenges and socioeconomic status. The problem of student absenteeism can be avoided if the school, teachers, parents and students take their respective roles so that this issues no longer happen among school students.